Արմավիրի մարզի Շահումյան գյուղի Թուխ Մանուկ մատուռը - Լիլիթ Հակոբյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Статья посвящена изучению святилища Тух Манук, которое находится в деревне Шаумян, Армавирская область. Эта часовня была построена в 2012 году и продолжает служить людям для исцеления и лечения. The article presents the sanctuary Tukh Manuk from the village Shahumyan, Armavir region. This chapel was built in 2012 and continues to serve the people for salvation and treatment.
Keywords: Christianity; Armenian church; History of the Armenian Church; Manners and customs